A novel measure of developing countries' agricultural and food policy readiness. (October 2022) - Oehmke, James F.; Young, Sera L.; Heinemann, Allen W.; Rukuni, Mandivamba; Lyambabaje, Alexandre; Post, Lori A.
Highlights: We introduce Rasch modeling to the quantification of a country's readiness to tackle agricultural policy issues. Rasch modeling provides a fundamental scale that solves the 'mash-up' index problem. Rwanda has a high degree of policy readiness, Kenya ranks low. Markets and trade policy, and mutual accountability, are difficult. Risk and resilience policy is least difficult. Abstract: Positive agricultural and food policy environments are critically important to the success and inclusiveness of agricultural growth and transformation. Despite the catalytic potential of enabling policies, countries vary in their willingness, capacity, and ability to improve policy: in other words they have varying degrees of policy readiness. The profession has spawned a plethora of 'policy readiness' indices over the past decade. These indices are welcome first steps, but they are non-statistical compilations of a collection of inherently different measures with unclear relationships: to borrow Ravallion's term, they are mash-up indices. In this paper we propose a novel, empirically-based policy readiness index. In contrast to prior literature, we approach the problem from a measurement perspective. This perspective enables us to aggregate items into a multi-component index such that their combination achieves superior statistical properties and assures cross-country comparability, through the application of Rasch modeling. With these empirical qualities, the meaning and robustness of the scores then become clear. We apply the model to a unique data set of policy actions prioritized in 2012/13, and the extent to which these actions were executed by Fall of 2015. The results are statistically- and measurement-valid measures of both country policy readiness and the degree of difficulty of various dimensions of policy actions. The resulting policy readiness scores are a novel index that significantly advances the dialogue on countries' abilities to execute those agricultural and food policy changes that are priorities for accelerating agricultural transformation. Policy implications include continued support for capacity building in low-readiness countries and cross-country support through continental or global processes for lowering the burden across all countries of making progress in the most difficult policy areas.